HAS DOMESTIC VIOLENCE REALLY INCREASED DURING THE COVID-19 PANDEMIC? AN EXAMPLE FROM TURKEY - E. Füsun KARAŞAHİN (Rojan GÜMÜŞ, 2024)
This study aims to evaluate the frequency of domestic violence based on court orders for treatment issued against perpetrators of domestic violence under Law No. 6284 on the Protection of Family and the Prevention of Violence against Women. We retrospectively analyzed violence cases reported by the court to the provincial health directorate under Law No. 6284 and information recorded by health workers about women who stated they were subjected to violence in 2019, 2020, and the first 6 months of 2021. The data were presented using descriptive statistics. Compared to the pre-pandemic period, the number of court orders for medical evaluation and treatment under Law No. 6284 increased by 333.4% in the first year of the pandemic. In the first 6 months of 2021, this number exceeded the total for 2020. More than half of the perpetrators had at least one addiction. Although health workers continue to provide service under the extreme circumstances brought about by the pandemic, they have a social responsibility to act with an awareness of violence in all areas of service provision (even contact tracing) and remain vigilant for signs of violence, especially in women.